2018
DOI: 10.3390/nu10050622
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Cost-Effectiveness and Equity Impacts of Restricting Television Advertising of Unhealthy Food and Beverages to Australian Children

Abstract: Television (TV) advertising of food and beverages high in fat, sugar and salt (HFSS) influences food preferences and consumption. Children from lower socioeconomic position (SEP) have higher exposure to TV advertising due to more time spent watching TV. This paper sought to estimate the cost-effectiveness of legislation to restrict HFSS TV advertising until 9:30 pm, and to examine how health benefits and healthcare cost-savings differ by SEP. Cost-effectiveness modelling was undertaken (i) at the population le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 33 publications
0
58
1
6
Order By: Relevance
“…The three most cost-effective interventions ('Alcohol price increase: uniform volumetric tax' [41], 'Sugar-sweetened beverages tax-20%' [21], and 'Restricting television advertising of unhealthy foods' [45]) were all regulatory interventions. The regulatory interventions appeared higher on the cost-effectiveness league table compared to program-based interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three most cost-effective interventions ('Alcohol price increase: uniform volumetric tax' [41], 'Sugar-sweetened beverages tax-20%' [21], and 'Restricting television advertising of unhealthy foods' [45]) were all regulatory interventions. The regulatory interventions appeared higher on the cost-effectiveness league table compared to program-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although we attempted to account for industry impacts in the evaluations, limited data availability meant that the impact on industry revenue resulting from regulatory interventions was not captured in the base case results, potentially underestimating the true cost of regulatory interventions. As part of the evaluation of one intervention ('Restricting television advertising of unhealthy foods' [45]), we conducted sensitivity analyses to include the impact of short term revenue losses to industry (television broadcasters) on cost-effectiveness results, and found that the intervention remained 'dominant'. For another intervention ('Restrictions on price promotions of sugar-sweetened beverages' [46]), we conducted a threshold analysis to determine the level of industry response at which the intervention would no longer be costeffective.…”
Section: Discussionmentioning
confidence: 99%
“…Future cost savings and benefits (HALYs) were discounted at 3% per year as per previous cost-effectiveness analyses for prevention interventions in Australia and are presented in 2010 values [5,14,31]. Incident cases of diseases saved were not discounted.…”
Section: Assessment Of Healthcare Cost Savingsmentioning
confidence: 99%
“…Previous studies investigating the health impacts of policies to reduce consumption of discretionary foods have shown that taxes, package size limits and restricting marketing of discretionary foods and drinks would result in considerable health benefits [5][6][7][8][9][10][11][12][13][14][15][16]. These studies have focused either on SSBs or on discretionary foods in general.…”
Section: Introductionmentioning
confidence: 99%
“…The ACE-Obesity Policy model is a multi-state, multiple cohort life table model that simulates the incidence, prevalence, and mortality related to nine obesity related diseases (i.e., type 2 diabetes, hypertensive heart disease, ischemic heart disease, stroke, osteoarthritis of the hip and knee, kidney cancer, colorectal cancer, endometrial cancer, and breast cancer) over the lifetime of the 2010 Australian population. The ACE-Obesity Policy model has been used to evaluate the economic credentials of various obesity policies in Australia [28][29][30][31] and details of the model have been previously published [27,32,33]. In brief, the model uses the prevalence of overweight and obesity taken from the Australian Health Survey 2010 [34] and relative risk estimates from the Global Burden of Disease (GBD) 2010 [35] to calculate the population impact fractions for nine obesity-related diseases.…”
Section: Health Outcomes Modelingmentioning
confidence: 99%